2014
DOI: 10.1007/s10661-014-3846-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural radioactivity in groundwater from the south-eastern Arabian Peninsula and environmental implications

Abstract: Groundwater is the most valuable resource in arid regions, and recognizing radiological criteria among other water quality parameters is essential for sustainable use. In the investigation presented here, gross-α and gross-β were measured in groundwater samples collected in the south-eastern Arabian Peninsula, 67 wells in Unite Arab Emirates (UAE), as well as two wells and one spring in Oman. The results show a wide gross-α and gross-β activities range in the groundwater samples that vary at 0.01∼19.5 Bq/l and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For these reasons, firstly, gross a and b activities in water resources need to determine without regard to the identity of specific radionuclides (WHO 2011). According to the recommended guideline, activity concentrations should be 0.5 Bq L -1 for gross a and 1.0 Bq L -1 for gross b activity concentrations in drinking water (WHO 2011;Murad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, firstly, gross a and b activities in water resources need to determine without regard to the identity of specific radionuclides (WHO 2011). According to the recommended guideline, activity concentrations should be 0.5 Bq L -1 for gross a and 1.0 Bq L -1 for gross b activity concentrations in drinking water (WHO 2011;Murad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the leaching of radionuclides from the aquifer was more favorable at higher temperatures, and these radionuclides were transported to the surface through groundwater circulation. This process has implications for the ecological environment and the health of surrounding residents (Murad A, et al, 2014). The researchers collected and analyzed water samples from hot springs and Zeliu Wells in the eastern Gonghe Basin to assess the natural radioactivity levels in the area.…”
Section: Introductionmentioning
confidence: 99%